RETRACTED: Assessing the Influencing Factors of Electronic Word-of-Mouth on CSR Issues. A Case of Hospotality Service Industry of China - Liu, Zhuo; Yu, Suihuai; Cheng, Fangmin; Waheed, Rida (Frontiers in Psychology, 2022)
Corporate social responsibility (CSR) information can be effectively disseminated via social media in a variety of industries, including the hospitality sector. In the same way, the media has a significant impact on CSR because the news media helps companies achieve their CSR goals. Prior research has not examined the main factors that influence electronic word of mouth (eWOM) on media coverage of CSR issues via social networking websites. For the purpose of examining the most significant predictors of intention to share or comment on negative CSR news reported by one media outlet on a specific social networking site (SNS). 677 Wechat users in China were surveyed in order to test the proposed model empirically. According to the findings of the study, eWOM intentions are positively influenced by environmental CSR content, and advertisement related CSR content. It also confirmed that the value of information is positively influenced by the credibility of the source. The variables interpersonal influencer impact and privacy concerns had no significant relationship, nor did they have any significant relationship with the intentions to share and comment on Wechat. Further the study findings suggest the theoretical and managerial policy recommendation for decision makers.